Environmental valuation model for greenhouse gases emission reduction due to the municipal recycling of solid waste in Brazil - Lima, Guilherme Cardim Gouveia de; Morais, Danielle Costa; Gomes, Susane de Farias; Fontana, Marcele Elisa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Solid waste management has become an increasingly important theme, since the space for the disposal of garbage in urban centers is limited and valued. The practice of recycling stands out as one of the best alternatives to reduce the volume of waste sent to landfills, reducing the emission of greenhouse gases (GHG) at the same time. As a form of promoting this practice, in 2007, a Brazilian Energy Company developed a program that gives discounts on energy bills upon delivery of recyclable materials. The program has recycled more than 13 thousand tons of waste, and granted more than R 1.5 million in rebates. In order to enable measurement of the environmental benefits of this program, this paper presents a model that relates the recycling of materials and the reduction in CO2 emissions that this practice produces. An application of the model shows that, in just 3 months, about 1,000 tons of CO2 was not emitted due to the program activities. The results show aluminum as the material which, when recycled, provides the largest reduction in emissions, and it is followed by paper/cardboard, steel, plastics, metals and glass.